Digital audio/speech forensics - Tok, De Fang. (2010)
MPEG-1 Audio Layer 3 (MP3) is one of or if not, the most common audio media format these days and with advancement in technology, portable devices like MP3 players or digital voice recorders can easily record MP3 while on the go. Sometimes, these MP3 recordings might be important evidences that need to be presented in a court hearing. The challenge therefore is how to ascertain the audio file authenticity especially when MP3 files can be doctored easily with pervasive audio editing software.